Republic of Kosovo : Selected Issues Paper. (IMF Staff Country Reports; Country Report ;, 2013)
This Selected Issues paper on the Republic of Kosovo's 2013 Article IV Consultation highlights growth and Kosovo's external environment. In the wake of the global financial crisis, Kosovo's economic growth slowed but remained positive, while most other Western Balkans slipped into recession. Moreover, the annual average growth rate has been among the highest in the Western Balkans since the onset of the financial crisis in 2007. Kosovo's tax-to-GDP ratio is comparable to the average of Southeastern Europe, although its tax system relies significantly more on indirect taxation-including a high share of trade taxes. Kosovo's reliance on trade taxes may create budgetary pressures in the event of further trade liberalization.